Integrity, Professionalism, and Job Performance: An Analysis of Determinants for Police Officers at the Police Officer Formation School-Lemdiklat Polri, Sukabumi, Indonesia - Mustaram, Mustaram (The International Journal of Business Review (The Jobs Review), 2023)
The objective of this research was to analyze the integrity and professionalism on performance toward job’s achievement. The method used was survey method with quantitative approach. The sample size was 310 Respondents that were an Policeman in Setukpa-Lemdiklat Sukabumi. The sampling technique was proportional random sampling in 4 batalyon. The data was collected by observation technique and questioner. Data Analysis technique used structural equation modeling (SEM) with AMOS Software. The result consist of four structural model showing the following result: (1)integrity and professionalism has significant effect on job’s achievement; (2) the integrity and professionalism has significant effect on performance; (3)the integrity and professionalism has significant effect on performance with the intervening of job’s achievement, and (4) the job’s achievement has significance effect on performance.